Systematic Review and Meta-analysis: Association of Aspirin With Incidence of Hepatocellular Carcinoma - Zhou, Xueliang; Zhang, Tengfei; Sun, Yali; Li, Chunwei; Ding, Xianfei; Zhu, Yanhui; Li, Lifeng; Fan, Zhirui (Frontiers in Pharmacology, 2022)
Abstract Aim: To explore the relationship between the use of aspirin and the incidence of hepatocellular carcinoma (HCC). Methods: MEDLINE, EMBASE, Web of Science and Cochrane CENTRAL databases were searched systematically from the earliest available date to March 13, 2020. The primary outcome was incidence of HCC, and the secondary outcomes were recurrence and mortality of HCC. The results were expressed as the Hazard Ratio (HR) and 95% confidence interval (CI). Based on the heterogeneity evaluated with the I2 statistic, a meta-analysis was performed using either a random- or fixed-effects model. Results: A total of sixteen articles (2781100 participants) were included. There was lower incidence of HCC in aspirin users than those in non-aspirin users (HR, 0.56; 95% CI, 0.46-0.69; P <0.001). Subgroup analysis further showed that the incidence of liver cancer in patients with alcoholic cirrhosis (HR, 0.14; 95% CI, 0.09-0. 22; P <0.001) and virus hepatitis (HR, 0.68; 95% CI, 0.62-0.74; P <0.001) who use aspirin was lower than that of patients who do not use aspirin. In addition, aspirin was found to associate with decreased risk of HCC mortality (HR, 0.71; 95% CI, 0.65-0.78; P <0.001), not HCC recurrence (HR, 0.52; 95% CI, 0.15-1.76; P = 0.291). Conclusions: Aspirin use is significantly associated with the low incidence rate of liver cancer.